2000
DOI: 10.1093/hmg/9.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal hypoplasia in humans and mice with PAX2 mutations: evidence of increased apoptosis in fetal kidneys of Pax21Neu +/- mutant mice

Abstract: PAX2 mutations cause renal-coloboma syndrome (RCS), a rare multi-system developmental abnormality involving optic nerve colobomas and renal abnormalities. End-stage renal failure is common in RCS, but the mechanism by which PAX2 mutations lead to renal failure is unknown. PAX2 is a member of a family of developmental genes containing a highly conserved 'paired box' DNA-binding domain, and encodes a transcription factor expressed primarily during fetal development in the central nervous system, eye, ear and uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(157 citation statements)
references
References 39 publications
9
145
0
1
Order By: Relevance
“…In previous studies, we have shown that PAX2 haploinsufficiency causes renal hypoplasia associated with reduced nephron number (oligonephronia), detectable in the early stages (E15) of kidney development in the mouse (9). Here, we confirm that heterozygous Pax2 1Neu fetal (E17.5) mice have a selective increase in apoptosis of UB cells; we also directly demonstrate a significant deficit in arborization of the PAX2 mutant UB.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In previous studies, we have shown that PAX2 haploinsufficiency causes renal hypoplasia associated with reduced nephron number (oligonephronia), detectable in the early stages (E15) of kidney development in the mouse (9). Here, we confirm that heterozygous Pax2 1Neu fetal (E17.5) mice have a selective increase in apoptosis of UB cells; we also directly demonstrate a significant deficit in arborization of the PAX2 mutant UB.…”
Section: Discussionsupporting
confidence: 84%
“…However, the highest levels of PAX2 expression during renal development are seen in the arborizing UB, and we have recently shown that it appears to suppress programmed cell death pathways in that lineage (8,9). PAX2 strongly suppresses apoptosis in cultured renal cells (8), and we noted a striking increase in apoptotic (TUNEL-positive) UB cells of E15 fetal kidneys of mice heterozygous for the PAX2 1Neu mutation (9). We have hypothesized (10) that the principal factor causing oligomeganephronia in RCS is loss of PAX2 anti-apoptotic function in the branching UB.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Inhibition of PAX2 in renal cell lines reduces proliferation as well as resistance to cisplatin treatment (26,28). Analyses of the Pax2 +/− kidney phenotype also support a role for Pax2 in cell survival (30)(31)(32)(33). Expression of PAX2 correlates with increased migration of Kaposi sarcoma cells and endothelial cells isolated from renal tumors (29,34).…”
Section: Introductionmentioning
confidence: 99%
“…66 similarly, reduced PaX2 signaling caused by a heterozygous Pax2 mutation has been shown to result in shortened intravesical ureters, caudally shifted ureteric buds, reduced bud branching, small hypoplastic kidneys with reduced nephron number and particularly vur. 51,67 the transcription factor Lim1 (also known as homeobox protein Lhx1) is a homeobox gene expressed in the organizer region of mouse embryos. Conditional knockout of Lim1 in the ureteric bud and mesonephric duct has been shown to delay bud formation, slow mesonephric duct migration to the bladder, and cause the kidneys to be small and malformed, with dilated refluxing ureters.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%